Kajian Formulasi Bacillus thuringiensis Dengan Carrier Limbah Cair Pabrik Kelapa Sawit Untuk Pengendalian Ulat Api (Setora nitens) - Wahyuono, Dwi (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
This research aims to examine palm oil effluent as a carrier for B. thuringiensis and its effectiveness against Setora nitens instar II-III in palm plantation. This research was held on April â December 2013 using single factor experiment method that has been arranging in completely randomized design (CRD). The research have two stages, first stage: development of B .thuringiensis and second stage: testing bioassay. First stage consist of three treatments that is 100%, 75%, 50% of Palm Oil Effluent and Luria Bertani Broth as a possitive control. Every treatment was added 0,4 g red sugar and 30 ml coconut water. the treatment in second stage same with first stage but use destilled water in addition treatment.Â  The parameter used are viability of B. thuringiensis, mortality (%), the speed of mortality, the change of population (%), and anti feedant (%). The result shown that palm oil effluent serve the purpose of alternative media of development B. Thuringiensis 7,6 x 107 CFU/ml. The optimal incubation period based of the toxcicity that is 48 hours. Formulation LCPKS 100% + 0,4 g red sugar + 30 ml coconut water + B. thuringiensis inclined more better based on the parameter of mortality, the change of population precentage, the speed of mortality amd anti feedant.